Roles and jobs in the open research scholarly communications environment: analysing job descriptions to predict future trends - Pontika, Nancy (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2019)
During the past two-decades academic libraries updated current staff job responsibilities or created brand new roles.  This allowed them to adapt to scholarly communication developments and consequently enabled them to offer efficient services to their users. The global calls for openly accessible research results has shifted the institutional, national and international focus and their constant evolvement has required the creation of new research positions in academic libraries. This study reports on the findings of an analysis of job descriptions in the open research services as advertised by UK academic libraries.METHOD: From March 2015 to March 2017, job advertisements relating to open access, repositories and research data management were collected.RESULTS: The analysis of the data showed that the primary responsibilities of the open research support staff were: to ensure and facilitate compliance with funders’ open access policies, maintain the tools that enable compliance, create reports and collect statistics that measure compliance rates and commit to continuous liaising activities with research stakeholders.DISCUSSION: It is clear that the open research services is a complex environment, requiring a variety of general and subject specific skill sets, while often a role may involve more than one area of expertise.CONCLUSION: The results of this study could benefit prospective employees and universities that wish to embed open research skills in their curriculum.